2005
DOI: 10.1681/asn.2004111006
|View full text |Cite
|
Sign up to set email alerts
|

Engagement of Transferrin Receptor by Polymeric IgA1

Abstract: IgA nephropathy (IgAN), the most common primary glomerulonephritis in the world, is characterized by IgA immune complex-mediated mesangial cell proliferation. The transferrin receptor (TfR) was identified previously as an IgA1 receptor, and it was found that, in biopsies of patients with IgAN, TfR is overexpressed and co-localizes with IgA1 mesangial deposits. Here, it is shown that purified polymeric IgA1 (pIgA1) is a major inducer of TfR expression (three- to four-fold increase) in quiescent human mesangial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 29 publications
1
65
0
1
Order By: Relevance
“…Recent studies have suggested that, in addition to reabsorbing the iron compounds filtered from the glomerulus, TfR might act as an immunoglobulin (Ig)A1 receptor and might be involved in the pathogenesis of IgA nephropathy (21,22). It remains of interest whether or not the modulation of TfR expression underlies the renoprotective effects of angiotensin II converting enzyme inhibitor and the AT1 receptor blocker in IgA nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that, in addition to reabsorbing the iron compounds filtered from the glomerulus, TfR might act as an immunoglobulin (Ig)A1 receptor and might be involved in the pathogenesis of IgA nephropathy (21,22). It remains of interest whether or not the modulation of TfR expression underlies the renoprotective effects of angiotensin II converting enzyme inhibitor and the AT1 receptor blocker in IgA nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…34 Moreover, CD71 on human mesangial cells effectively binds immune complexes containing galactose-deficient IgA1, leading to enhanced expression of CD71. 35,36 This binding creates a positive feedback loop, causing overexpression of CD71 on proliferating mesangial cells. However, it is not known whether CD71 is the only receptor that binds IgA1-containing immune complexes or whether it has a direct pathogenic role in IgAN.…”
Section: Hit 3: Formation Of Pathogenic Iga1-containing Immune Complexesmentioning
confidence: 99%
“…Recent evidence also exists that mesangial cells are activated by aberrantly glycosylated IgA1 via binding transferrin receptor, with induction of proliferation and release of IL-6 and TGF-␤. 31 Taken together, these data suggest an important role for the spatial organization of IgA and C3c within the immune deposits in influencing the glomerular inflammatory response in IgAN. It is tempting to speculate that the presence of variable , there is prevalence of exposed IgA, whereas in B (case 9), there is marked increase of exposed C3c, with several deposits lacking surface IgA.…”
Section: Discussionmentioning
confidence: 70%